1996
DOI: 10.1021/bi952862w
|View full text |Cite
|
Sign up to set email alerts
|

Role of a Disulfide-Bonded Peptide Loop within Human Complement C9 in the Species-Selectivity of Complement Inhibitor CD59

Abstract: CD59 antigen is a membrane glycoprotein that inhibits the activity of the C9 component of the C5b-9 membrane attack complex (MAC), thereby protecting human cells from lysis by human complement. The complement-inhibitory activity of CD59 is species-selective, and is most effective toward C9 derived from human or other primate plasma. The species-selective activity of CD59 was recently used to map the segment of human C9 that is recognized by this MAC inhibitor, using recombinant rabbit/human C9 chimeras that re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…Whereas definitive identification of the residues forming the active site of CD59 awaits a direct demonstration of which side chains of the protein actually contact the C8 and C9 components of MAC, it is of interest to note the following. (i) In the case of both human C8␣ and C9 polypeptides, the peptide segment within each protein that has been directly shown to provide the specific binding site for attachment of human CD59 to these complement components represents a distinct region within each polypeptide that is most notable for marked divergence in aligned sequence when human C8␣ and C9 are each compared with its corresponding polypeptide of rabbit and other species (7)(8)(9)26). This suggests that the motif within each of these complement proteins to which CD59 attaches has itself undergone considerable evolutionary drift relative to other portions of the polypeptide, implying a similar evolutionary drift of the complementary binding site in CD59 as would be required to maintain interaction between the proteins.…”
Section: Identity Of Residues In Cd59 That Confer Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas definitive identification of the residues forming the active site of CD59 awaits a direct demonstration of which side chains of the protein actually contact the C8 and C9 components of MAC, it is of interest to note the following. (i) In the case of both human C8␣ and C9 polypeptides, the peptide segment within each protein that has been directly shown to provide the specific binding site for attachment of human CD59 to these complement components represents a distinct region within each polypeptide that is most notable for marked divergence in aligned sequence when human C8␣ and C9 are each compared with its corresponding polypeptide of rabbit and other species (7)(8)(9)26). This suggests that the motif within each of these complement proteins to which CD59 attaches has itself undergone considerable evolutionary drift relative to other portions of the polypeptide, implying a similar evolutionary drift of the complementary binding site in CD59 as would be required to maintain interaction between the proteins.…”
Section: Identity Of Residues In Cd59 That Confer Functionmentioning
confidence: 99%
“…This implies that the CD59 homologue expressed on the surface of rabbit cells is also selective for homologous complement and cannot effectively interact with the human C8 and C9 components to inhibit MAC. We have previously taken advantage of the species selectivity inherent to the interaction of CD59 with C8 and C9 to map the peptide-binding sites within the human C8 and C9 proteins that are recognized by human CD59 (7,8,26). In those studies, the capacity of human CD59 to inhibit MAC assembly was measured using recombinant human/rabbit chimeras of C8 and C9 in order to identify the residues within the C8␣ and C9 polypeptides that are specifically required to confer recognition of these complement components by human CD59.…”
mentioning
confidence: 99%
“…17,18,[25][26][27][28][29] Recently, we developed a novel, potent, non-toxic and specific antihCD59 inhibitor: the domain 4 of intermedilysin (ILY). This inhibitor is defined as rILYd4.…”
Section: Introductionmentioning
confidence: 99%
“…142,143 (ii) Peptides derived from C8 and C9: extensive studies of hCD59 structure, as well as of its interaction with C8 and C9, revealed the region of hCD59 critical for inhibiting MAC formation through preventing binding of C8 and C9. [144][145][146][147][148] Small peptides derived from C8 and C9 that bind to this region are effective against hCD59 function at concentrations greater than 300 mmol/l of IC 50 , limiting their therapeutic usefulness. 147,148 Recently, we reported the development of a recombinant form of the fourth domain of the bacterial toxin intermedilysin (rILYd4), a 114 amino-acid protein that inhibits human CD59 function with high affinity and specificity.…”
Section: Complement Activation In Hiv-1 Infection Qg Yu Et Al 336mentioning
confidence: 99%